Managing Object Oriented Software Understandability: A Design Perspective (International Journal of Innovative Research in Computer Science & Technology, 2020)
Estimating understandability of object  oriented software early in the development process;  particularly at design phase greatly reduce the overall  development cost and effort. To design and deliver quality  products inside time and financial plan understandability  plays a very important role. This paper shows the need and  significance of understandability at design phase and build  up a multivariate linear model “Understandability  Estimation Model” for Object-Oriented Design. Developed  model estimates the understandability of class diagrams in  respect of their internal design properties. In this research  paper an attempt has been made to propose an  understandability estimation framework as a first  contribution. A relation between object oriented design  properties and understandability has been established as a  second contribution. In third contribution, despite the fact  that, in order to estimate class diagram’s understandability  the researcher further developed multivariate models. In  conclusion the proposed Understandability models have been authenticated via experimental test.
Keywords: Understandability; Modifiability; Object Oriented Software; Design Phase; Design Construct